Innovational Transformational Leadership on the era Digital Post Pandemic Covid-19 in the hospitality industry : A Review - Simatupang, Monika (Universitas Pelita Harapan, 2024)
The research aims to understand better leadership strategies that foster innovation, improve operational efficiency, and enhance employee adaptability during digital transformation initiatives. The study employs a qualitative approach, conducting a critical literature review of 30 academic sources focused on transformational leadership and digital transformation in the hospitality sector. This research presents a conceptual framework illustrating how transformational leadership drives successful digital transformation by fostering innovation and technological integration. The findings reveal that transformational leaders enhance employee adaptability, operational efficiency, and customer engagement, making digital transformation a core component of organizational resilience. However, the findings offer practical insights for leaders seeking to implement digital transformation strategies while navigating post-pandemic challenges, such as fostering a culture of innovation, investing in employee training, and leveraging digital tools for operational efficiency. This study provides a novel combination of transformational leadership and digital transformation concepts within the post-pandemic hospitality industry, filling a significant gap in the existing literature. It highlights the importance of leadership strategies integrating digital tools to foster innovation and resilience in the hospitality sector.